Analisis Kredit Mantap Pensiun Dalam Meningkatkan Kesejahteraan Nasabah Pensiun Di PT Bank Mandiri Taspen KCP Baturaja - Sayu Mainingsih; Rofiqoh Rofiqoh; Yunika Nanda Putri (Kafalah: Jurnal Ekonomi, Manajemen, dan Keuangan Syariah, 2026)
This study is entitled “Analysis of Kredit Mantap Pensiun in Improving the Welfare of Retired Customers at PT Bank Mandiri Taspen KCP Baturaja,” which discusses how the Kredit Mantap Pensiun (KMP) product is implemented in improving the welfare of retired customers at PT Bank Mandiri Taspen KCP Baturaja, as well as the supporting and inhibiting factors in its implementation. This study aims to gain an in-depth understanding of how the KMP product is implemented in improving customer welfare and to identify the supporting and inhibiting factors in the implementation of the KMP product for retired customers at PT Bank Mandiri Taspen KCP Baturaja.The type of research used is descriptive research with a qualitative approach. The data sources consist of primary and secondary data. Data collection techniques include interviews, observations, and documentation.The results of the study indicate that the KMP product provision process consists of ten stages: credit application submission, verification and completion of required documents, interviews, on-the-spot visits, credit analysis, signing of the credit application, credit approval, credit disbursement, credit monitoring, and credit recovery. The KMP product helps improve the welfare of retired customers by assisting them in meeting consumptive needs and alleviating their financial burden in fulfilling increasingly high living expenses and urgent needs.Based on the research findings, supporting factors in the implementation of KMP include having human resources who are knowledgeable about the credit products offered, cooperation with BKPSDM and KPPN offices in the OKU Induk, OKU Timur, and OKU Selatan regions for pension administration and product promotion, as well as the availability of mobile service vehicles to accelerate services for retired customers outside the OKU Induk area. Meanwhile, several obstacles were identified in the KMP provision process, such as incomplete required documents, discrepancies in customer personal data, prospective customers having existing loans at other banks or financial institutions, network issues during video calls, and competition from other banks or financial institutions.